Andragogy Approach in the Utilization of Liquid Smoke Coconut Waste as a Vegetable Insecticide for Coconut Farming Community - Wahyu Ana Pria Utama , (Jurnal Serambi Ilmu, 2024)
Appropriate technology learning must be able to touch all levels of society. In this research, we combine formal education with informal education in the form of participatory education for adults. Participatory education is intended to involve the community directly participating in the implementation of this research by seeing, doing, and observing the process. The aim is how to utilize liquid smoke from coconut frond waste as a vegetable insecticide as well as a repellent or insect repellent because it contains phenol or phenolic, antioxidant, antimicrobial in coconut plants in the people of Aceh Besar. Based on the results of chemical analysis in liquid smoke found elements or chemical substances, such as acetic acid, carboxyl and phenol. This study aims to determine how the effect of temperature and duration of combustion on the yield (final product), such as the degree of acidity, acetic acid content, and phenol content. This research was carried out using a factorial Completely Randomized Design (CRD) with two main factors, namely: Factor-1 burning for 2-3 hours and Factor-2 with variations in temperature 200oC, 250oC, 300oC, 350oC, 400oC. The best result for liquid smoke is 25% (w/w) of 20 kg of dry matter from coconut fronds. The average content of acetic acid (CH3COOH) is 6.45 mg/ml. And the content of phenol (C6H6O) is 3.76 ppm.